Colistin and anti-Gram-positive bacterial agents against Acinetobacter baumannii - Liu,Bin (2014)
Introduction Acinetobacter baumannii has attained an alarming level of resistance to antibacterial drugs. Clinicians are now considering the use of older agents or unorthodox combinations of licensed drugs against multidrug-resistant strains to bridge the current treatment gap. We investigated the in vitro activities of combination treatments that included colistin with vancomycin, norvancomycin or linezolid against multidrug-resistant Acinetobacter baumannii. Methods The fractional inhibitory concentration index and time-kill assays were used to explore the combined effects of colistin with vancomycin, norvancomycin or linezolid against 40 clinical isolates of multidrug-resistant Acinetobacter baumannii. Transmission electron microscopy was performed to evaluate the interactions in response to the combination of colistin and vancomycin. Results The minimum inhibitory concentrations (MICs) of vancomycin and norvancomycin for half of the isolates decreased below the susceptibility break point, and the MIC of linezolid for one isolate was decreased to the blood and epithelial lining fluid concentration using the current dosing regimen. When vancomycin or norvancomycin was combined with subinhibitory doses of colistin, the multidrug-resistant Acinetobacter baumannii test samples were eradicated. Transmission electron microscopy revealed that subinhibitory doses of colistin were able to disrupt the outer membrane, facilitating a disruption of the cell wall and leading to cell lysis. Conclusions Subinhibitory doses of colistin significantly enhanced the antibacterial activity of vancomycin, norvancomycin, and linezolid against multidrug-resistant Acinetobacter baumannii.